Problem-Solving Ability In Arithmetic Sequences And Series Using Problem-Based Learning - Mariana Marta Towe (Universitas Veteran Bangun Nusantara, 2026)
This study aims to describe the learning process on the topic of sequences and series using the Problem-Based Learning (PBL) approach, and to describe students' mathematical problem-solving abilities on the topic of arithmetic sequences and series using the Problem-Based Learning (PBL) approach. The study was conducted at SMA Negeri 1 Adonara Tengah in February 2026. The subjects of this study were 16 students in Grade XI. The data collection techniques used were learning process, written tests, and interviews. Mathematics learning on the topic of sequences and series using the PBL approach was carried out through several stages: (a) orientation, (b) organizing, (c) guiding individual/group investigation, (d) developing and presenting, and (e) analyzing and evaluating. The results of the written test from 16 students, analyzed based on indicators of mathematical problem-solving ability, showed that for Problem 1, all 16 students (100%) were classified as having high problem-solving ability, having met indicators 1–4; for Problem 2, 13 students (81.25%) were classified as having high problem-solving ability, having met indicators 1–4, while 3 students (18.75%) were classified as having moderate problem-solving ability, having only met indicators 1–2. Based on the results obtained, it can be concluded that mathematics learning on the topic of sequences and series using the PBL approach can improve students' problem-solving abilities.